Functional and biochemical properties of Mal de Río Cuarto virus (Fijivirus, Reoviridae) P9-1 viroplasm protein show further similarities to animal reovirus counterparts - Maroniche, Guillermo Andrés (2010)
Mal de Río Cuarto virus (MRCV) is a plant virus of the genus Fijivirus within the family Reoviridae that infects several monocotyledonous species and is transmitted by planthoppers in a persistent and propagative manner. Other members of the family replicate in viral inclusion bodies (VIBs) termed viroplasms that are formed in the cytoplasm of infected plant and insect cells. In this study, the protein coded by the first ORF of MRCV segment S9 (P9-1) was shown to establish cytoplasmic inclusion bodies resembling viroplasms after transfection of Spodoptera frugiperda insect cells. In accordance, MRCV P9-1 self-associates giving rise to high molecular weight complexes when expressed in bacteria. Strong self-interaction was also evidenced by yeast two-hybrid assays. Furthermore, biochemical characterization showed that MRCV P9-1 bound single stranded RNA and had ATPase activity. Finally, the MRCV P9-1 region required for the formation of VIB-like structures was mapped to the protein carboxy-terminal half. This extensive functional and biochemical characterization of MRCV P9-1 revealed further similarities between plant and animal reovirus viroplasm proteins.